2017
DOI: 10.1155/2017/4934198
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Levels and Risk Factors among Preschool Children in a Lead Polluted Area in Taizhou, China

Abstract: Objective. To determine the blood lead levels and identify related risk factors among preschool children in a lead polluted area (Taizhou, China) and provide theoretical support for prevention of lead pollution. Methods. A stratified-clustered-random sampling method was used to determine the survey sample. Blood lead levels were determined by the tungsten atomizer absorption spectrophotometer. Results. A total of 2,018 subjects (average age of 59 months; 1,087 boys and 931 girls) were included. The arithmetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
2
9
0
1
Order By: Relevance
“…One-year-old children had the highest proportion (65%) of BLLs < 5 µg/dL. This finding is consistent with a 2017 study in a community with lead smelting, battery production and production of lead-containing chemicals in China that found the highest BLLs were among children ages 3–5 years [25]. The increase in BLLs with age might result from older children being more likely to have activities outside the home, creating greater contact with potential sources of lead exposure (e.g., soil and dust).…”
Section: Discussionsupporting
confidence: 89%
“…One-year-old children had the highest proportion (65%) of BLLs < 5 µg/dL. This finding is consistent with a 2017 study in a community with lead smelting, battery production and production of lead-containing chemicals in China that found the highest BLLs were among children ages 3–5 years [25]. The increase in BLLs with age might result from older children being more likely to have activities outside the home, creating greater contact with potential sources of lead exposure (e.g., soil and dust).…”
Section: Discussionsupporting
confidence: 89%
“…Lead toxicity is a worldwide public health hazard. There is no completely safe blood lead level (BLL) to date – even 5 μg/dL - and damage may occur at low BLL [ 4 , 5 ]. Even though developed countries promoted environmental regulations to lower lead poisoning rates, developing countries still represent high rates of lead toxicity, especially in the children [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of children with symptoms of excessive blood lead had the following characteristics: their homes were near factories, garages and construction sites around the residential area [ 67 ], the distance from downtown or a commercial street was less than 500 m [ 68 , 69 ] ( Table 14 ). Gao [ 70 ] and Li [ 67 ], in their own studies indicated that the above characteristics were risk factors for elevated blood levels in children. Previous studies have shown that the closer the ground was, the higher the concentration of lead in the atmosphere was.…”
Section: Resultsmentioning
confidence: 99%